2017
DOI: 10.1002/cbdv.201600345
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils from Different Morphological Parts of Pinus cembra L.

Abstract: The essential oils from needles, twigs, bark, wood, and cones of Pinus cembra were analyzed by GC-FID, GC/MS, and H-NMR spectroscopy. More than 130 compounds were identified. The oils differed in the quantitative composition. The principal components of the oil from twigs with needles were α-pinene (36.3%), limonene (22.7%) and β-phellandrene (12.0%). The needle oil was dominated by α-pinene (48.4%), whereas in the oil from bark and in the oil from twigs without needles there were limonene (36.2% and 33.6%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
(22 reference statements)
4
11
0
Order By: Relevance
“…3‐Carene occurred in the dextrorotary form, whereas α ‐pinene in both, dextro‐ and levorotary forms ( Table ). Similar proportions of these monoterpene hydrocarbons were previously found in the monoterpene fractions of the oils of Pinus cembra , P. nigra , P. pinaster , and P. sylvestris . Oxygenated monoterpenes in the essential oil from twigs with needles of P. mugo were represented by bornyl acetate (4.5 %) and α ‐terpinyl acetate (2.4 %), sesquiterpenes by germacrene D (1.7 %).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…3‐Carene occurred in the dextrorotary form, whereas α ‐pinene in both, dextro‐ and levorotary forms ( Table ). Similar proportions of these monoterpene hydrocarbons were previously found in the monoterpene fractions of the oils of Pinus cembra , P. nigra , P. pinaster , and P. sylvestris . Oxygenated monoterpenes in the essential oil from twigs with needles of P. mugo were represented by bornyl acetate (4.5 %) and α ‐terpinyl acetate (2.4 %), sesquiterpenes by germacrene D (1.7 %).…”
Section: Resultssupporting
confidence: 74%
“…The chemical composition of the essential oils was determined by chromatographic and spectroscopic methods (GC/FID, GC/MS, 1 H‐NMR). The apparatus and conditions for all analyzes have been previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatile components of L. stoechas presented in this study were both similar and different from previously reported studies . For instance, our results are in agreement with those of Matos et al., which reported that fenchone was a key component in the essential oil of L. stoechas .…”
Section: Resultssupporting
confidence: 86%
“…There are many references about essential oil composition of pines [4][5][6][7][8], even on population level [9][10][11], etc. However, there are only few reports of Swiss stone pine dealing with composition of terpenes [12,13], their enantiomers [14] and/or their antioxidant and antimicrobial activities [2].The most detailed is the report of Lis et al [15] who examined essential oils from different parts of P. cembra.…”
mentioning
confidence: 99%